The Effect of Liquidity Management on the Company's Financial Performance - Amelia, Rizki; Pratama, Bayu Aji; Lestari, Henny Setyo (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
This study aims to assess the impact of liquidity management on the financial performance of companies in the consumer cyclical sector listed on the Indonesia Stock Exchange (IDX) during the period of 2019-2023. The primary focus of the research is to examine the effect of three liquidity ratios—Current Ratio (CR), Quick Ratio (QR), and Cash Ratio (CR)—on Return on Capital Employed (ROCE). Using a purposive sampling method, 50 companies that met the criteria were included in the analysis, which was conducted using panel data regression. The results show that none of the liquidity variables had a significant impact on ROCE, indicating that the company's liquidity level does not directly determine the performance of the capital used to generate profits in this sector. These findings provide valuable insights for companies and investors, suggesting that liquidity is not the only determining factor in capital management and profitability strategies. Therefore, companies and investors need to consider other variables that may influence financial performance, such as capital structure, operational efficiency, and market conditions, when formulating business strategies and investment decisions.